RESEARCH ON THE TECHNOLOGICAL PARAMETERS OF ORANGE RAKIA PRODUCTION - Tuan Anh, Ho; Quang Tu, Pham (HNUE Journal of Science: Journal of Natural Sciences, 2025)
This research aims to identify the technological parameters involved in the production of rakia from Ha Giang oranges. The fermentation must was prepared by adding the disinfectant and antioxidant K2S2O5 at a concentration of 150 mg/L to ensure the sterility and stability of the orange juice for the subsequent fermentation stage. Using the native yeast strain Saccharomyces cerevisiae HB2 isolated from oranges, the factors influencing the fermentation process were determined, including fermentation temperature of 30oC, initial total soluble solids after adding sugar of 20°Bx, initial yeast cell density of 8.5 x 106 CFU/mL, and pH of 4.1. At the pilot scale of 5 liters, after fractional distillation and the removal of 3% ethanol from the head and 3% from the tail fractions, the resulting heart fraction had an alcohol concentration of 53% vol. After dilution to a final alcohol concentration of 35% vol by distilled water, the finished rakia had a characteristic orange aroma. The sensory score achieved was 18.16, which is in the ‘good’ category.